Perlindungan Hukum Terhadap Tenaga Kerja Indonesia Yang Mengalami Human Trafficking - Iskandar Gafur Tuasikal; Josina Augustina Yvonne Wattimena; Veriana Josepha Rehatta (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Human Trafficking is a form of transnational crime. In 2018 the Police Headquarters of the Republic of Indonesia revealed that there were at least 1,200 (one thousand two hundred) people who were victims of trafficking in persons from Indonesia who were ready to be sent to the Middle East.Purposes of the Research: This writing aims to find out and examine forms of protection for Indonesian workers who experience human trafficking. Methods of the Research: The type of legal research carried out is normative juridical, with sources of legal material in the form of primary and secondary legal materials. The problem approach is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials is done by first collecting primary legal materials and then linking them with secondary legal materials. The processing and analysis of legal materials is described qualitatively.Results of the Research: The principle of earlier forms of protection talks about legal liability, with reference to the general principle in which protection for Indonesian workers is prioritized on two things, namely protection and prevention. As for protection and prevention, it is more to the preventive aspect, while the repressive concept is more to strict rules.